2020
DOI: 10.17129/botsci.2445
|View full text |Cite
|
Sign up to set email alerts
|

Conyza sumatrensis allelopathy effect on Bidens pilosa (Asteraceae) seed germination

Abstract: Background: Other tools for weed management should be considered in addition to the use of herbicides. In this context, the identification and use of allelopathic compounds deserves attention. Question: To quantify phenolic compounds and evaluate the allelopathic potential of extracts of Conyza sumatrensis on the germination of Bidens pilosa. Studied species: Conyza sumatrensis (Retz.) E.Walker, Bidens pilosa L. (Asteraceae) Study site: Palotina, state of Paraná, Brazil. Methods: The aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, in the present study, it was found that Cuscuta reflexa is rich in phenolics and flavonoids that might have negatively affected the seed germination process at higher doses by restricting the activities of germination enzymes. Ferreira et al [ 81 ] reported that high concentrations of leaf and root extract of Conyza sumatrensis adversely affected the seed germination and seedling emergence of Bidens pilosa , and this decrease might be attributed to the high levels of phenolics and flavonoids in the extract. Rizzardi et al [ 82 ] reported that 6 and 8% concentration of extracts from the shoots of canola reduced the germination of Bidens sp., while Reik [ 83 ] recorded a reduction in the germination percentages of B. pilosa treated with the aqueous extracts at levels higher than 30% concentration (v/v).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the present study, it was found that Cuscuta reflexa is rich in phenolics and flavonoids that might have negatively affected the seed germination process at higher doses by restricting the activities of germination enzymes. Ferreira et al [ 81 ] reported that high concentrations of leaf and root extract of Conyza sumatrensis adversely affected the seed germination and seedling emergence of Bidens pilosa , and this decrease might be attributed to the high levels of phenolics and flavonoids in the extract. Rizzardi et al [ 82 ] reported that 6 and 8% concentration of extracts from the shoots of canola reduced the germination of Bidens sp., while Reik [ 83 ] recorded a reduction in the germination percentages of B. pilosa treated with the aqueous extracts at levels higher than 30% concentration (v/v).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the amount of weed straw may not have been enough to release allelopathic compounds on soybean. While (19) it was reported a negative effect of aqueous extracts of Conyza sumatrensis (from roots and shoots) on seed germination of Bidens pilosa, with an increase due to the increased concentration of extracts, as well as a stronger effect for the root extracts. Similar to observed for D. insularis extracts on canola germination (34).…”
Section: Discussionmentioning
confidence: 98%
“…The RC and PT extracts reached GSI equal to zero at a concentration of 25 g L −1 and the JG extracts at 45 g L −1 . The GSI is proportional to seed vigor, indicating that higher values represent more vigorous seeds 24 . In our study, seed vigor was significantly reduced due to the interference of the phytotoxic allelochemicals contained in the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…They can increase the permeability of the cell membrane, causing the spread of cell contents and increasing lipid peroxidation, causing the slow growth or death of plant tissue and inhibiting nutrient absorption from the environment, affecting the normal growth of plants 42 . Phenolic acids, specifically, can act by inducing an increase in the activity of oxidative enzymes, causing changes in membrane permeability and lignin formation and contributing to the reduction of plant root growth 24 .…”
Section: Resultsmentioning
confidence: 99%